2005
DOI: 10.1002/jbm.a.30447
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of calcium titanate as apatite growth promoter

Abstract: Calcium titanate (CaTiO(3), perovskite) has been used to determine its apatite nucleation ability and propose a possible nucleation initial step. Measurements of calcium leaching from the calcium titanate surface and phosphate adsorption experiments were carried out separately by using commercial calcium titanate suspensions at room temperature. Adsorption behaviour determined by zeta potential measurements shows that phosphate is strongly adsorbed on the calcium titanate surface. It was found that the higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 31 publications
4
43
1
Order By: Relevance
“…The resolution capability of our XPS apparatus was relatively low so that we could not obtain similar results; in our case, however, some Ca on the surface of titanium may also be present as calcium titanate. In addition, the surface of calcium titanate reportedly releases some Ca ions [22]. In this context, the state of surface Ca on the surface of titanium hydrothermally treated with CaCl 2 could be presumed to comprise both ion and stable compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resolution capability of our XPS apparatus was relatively low so that we could not obtain similar results; in our case, however, some Ca on the surface of titanium may also be present as calcium titanate. In addition, the surface of calcium titanate reportedly releases some Ca ions [22]. In this context, the state of surface Ca on the surface of titanium hydrothermally treated with CaCl 2 could be presumed to comprise both ion and stable compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that calcium titanate releases Ca ions, thereby forming a surface richer in TiO 2 , which would in turn transform TiOH groups. Both surface Ca and TiOH sites then adsorb phosphate ions, which may cause apatite nucleation on its surface [22]. In this context, the surface Ca layer may contribute to protein/ cell adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…These powders were mixed homogeneously, shaped and sintered into disc of diameter 5-6 mm and thickness of 1-2 mm. Details of sample preparation are given in our earlier reports [9]. Dielectric and pyroelectric measurements were conducted on these samples.…”
Section: Methodsmentioning
confidence: 99%
“…BaTi03 and CaTi03, belonging to the same perovskite family and being bio-friendly materials, have been tried for the synthesis of HAp:BTO and HAp:CTO composites. The CTO has proven to be a good substrate for the apatite growth since it provides a positive surface charge that interacts with the negatively charged phosphate ions in the fluid [9]. This paper focuses on the measurements of dielectric and pyroelectric current generation characteristics of the synthesized composites as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 -based bioactive ceramic suggests that bone grafting is achieved by supporting the precipitation of calcium (Ca) and phosphorus (P) into a structure similar to the mineral phase of bone. Accordingly, titanium is very promising to develop biomedical materials and devices designed as hard tissue substitutes with improved interface properties (Coreno & Coreno, et al 2005;Hench, 1991;Li, et al, 1996;Kitsugi et al, 1996).…”
Section: Applicationsmentioning
confidence: 99%